Materials science and technology :a comprehensive treatment /. Volume 4, Electronic structure and properties of semiconductors / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Wolfgang Schroter - Schroter, Wolfgang.
Vol. 4 Electronic structure and properties of semiconductors in 1991